The Library as a Form of Cultures Communication - T. B. Markova (Дискурс, 2019)
Introduction. The increased interest to the history of book cultures, cultural linkages, and expanding international contacts between libraries has led to the search for new models for book and cultural exchange. Library as a social institution is one of the important elements of society, integrated into its socio-political, ideological and valuable structure. In addition to cultural historical documents it provides socially meaningful information to various segments of the population, is engaged in archiving of information, identify its importance and validity. Thereby satisfying the diverse needs of the meaningful information becomes a mediator between knowledge and society, between author and reader. Changes in the political, social and spiritual spheres, impact on activities of libraries. The study of the communicative practices acquires special importance. International cooperation can be attributed to forms of cultural interaction, as example it can be the exchange of not only books but also of information technology.Methodology and sources. Methodologically, the work is based on cultural-historical and socio-philosophical analysis of the research literature.Results and discussion. Library is considered as a medium of intercultural communication as a form of relationship cultures. Its main function is to preserve and promote the cultural diversity, the development of ethnic and national traditions of the society. Libraries are a form of cultural and information exchange. Therefore, the information approach needs to be supplemented with socio-philosophical and culturological approach, considering the library as a form of interrelation of cultures. Their reorganization on this basis will facilitate the formation of intellectually and culturally educated humanity, which will solve the conflict peacefully through dialogue and cooperation.  The result of this research is the understanding of the role of libraries in the extension and development of the world communities in the Search for optimal ways of meeting the reader and the book, effective methods of development of texts contributes to the solution of problems of intercultural communication.Conclusion. Globalization and digitization are changing the ways of communication, reading and understanding the information. Increase diversity of resources stimulate interest in selfeducation and distance learning. Currently, the role of libraries in the document-information processes, archiving and reporting. They become an effective platform for self-learning and online learning. The reader perceives a book together text and visual forms, using as a search tool of information and interactive technology, and various Internet resources. In addition, libraries are focused on international cooperation and cultural dialogue. The organization of visiting exhibitions, creation of global information resources, book presentations and publishing projects promote the cultural heritage and book collections.